Assessing the predictive value of a neuropsychological model on concurrent function in acute stroke recovery and rehabilitation. Issue 5 (4th July 2019) - Leitner, Damian; Miller, Harry; Libben, Maya
Abstract: Objective: Few studies have examined the relationship between cognition and function for acute stroke inpatients utilizing comprehensive methods. This study aimed to assess the relationship of a neuropsychological model, above and beyond a baseline model, with concurrent functional status across multiple domains in the early weeks of stroke recovery and rehabilitation. Method: Seventy-four acute stroke patients were administered a comprehensive neuropsychological assessment. Functional domains of ability, adjustment, and participation were assessed using the Mayo-Portland Adaptability Inventory - 4 (MPAI-4). Hierarchical linear regression was used to assess a neuropsychological model comprised of cognitive tests scores on domains of executive function, memory, and visuospatial-constructional skills (VSC), after accounting for a baseline model comprised of common demographic and stroke variants used to predict outcome. Results: The neuropsychological model was significantly associated, above and beyond the baseline model, with MPAI-4 Ability, Participation, and Total scores (all p -values < .05). The strength of association varied across functional domains. Analyzing tests of executive function, the Color Trails Test-Part 2 predicted MPAI-4 Participation ( β = −.46, p = .001), and Total score ( β = −.32, p = .02). Conclusion: Neuropsychological assessment contributes independently to the determination of multiple domains of functional function, above and beyond common medical variants of stroke, in the early weeks of recovery and rehabilitation. Multiple tests of executive function are recommended to develop a greater appreciation of a patient's concurrent functional abilities.